The Role of Human Resources Management in Improving the Performance of Employees of the Social and Community Empowerment Service of Samarinda City - Zainatun Nisa; Dito Aditia Darma Nasution (Journal of Indonesian Management, 2023)
Position planning, workforce planning, recruitment and selection, training and development, career planning, work performance evaluation, and transparent compensation are all aspects of human resource management, or HRM. The study employs a qualitative approach. Research site: Samarinda City Jl., Office of Social Affairs and Community Empowerment Dahlia False 12, Kec, Bugis 75121 in the city of Samarinda, East Kalimantan. Researchers have discovered that the Samarinda City Social and Community Empowerment Services human resource management plays a significant role in boosting employee performance. Performance.